The Pedagogy of Philosophical Inquiry (PI) to develop critical thinking and self-confidence among Muslim students - Abdullah, Norillah; Hashim, Rosnani (2009)
The purpose of this paper is to confirm the Muslim scholar views that philosophy philosophy can be used as a tool to enhance thinking. This study employed the pedagogy of Philosophical Inquiry (PI) among the undergraduate students of the Kulliyyah (Faculty) of Islamic Revealed Knowledge and Human Sciences (IRKHS), International Islamic University, Malaysia (IIUM). Besides that, it also aimed to find out how students view the approach. This study employed a qualitative approach. In the treatment group, students were taught using the PI approach, while in the control group, students were offered the regular formal critical-thinking skill course. Qualitative analysis from the assignments showed that the treatment group was able to apply more critical thinking skills in their answers as compared to the control group. In addition, the treatment group was inclined to raise more philosophical questions or higher order questions while the control group was inclined to raise more factual questions or lower order questions. Findings from the interviews and journal entries of the treatment group, showed that through the process of dialogue and discussion among students, they felt that a change had occurred in their way of thinking. They learned how to express their views and how to support their arguments with good reasons and examples and at the same time they learned to organise their arguments more systematically. They were exposed to different perspectives given by others and consequently, they became more open. It improved their self-confidence especially in expressing their ideas openly in front of others.